The timing of perinatal hypoxia/ischemia events in term neonates: a retrospective autopsy study. HSPs, ORP-150 and COX2 are reliable markers to classify acute, perinatal events - Rabozzi Roberto; Pomara Cristoforo; Ventura Francesco; Fulcheri Ezio; De Stefano Francesco; Neri Margherita; Riezzo Irene; Turillazzi Emanuela; Fineschi Vittorio (Diagnostic Pathology, 2010)
Abstract Background The understanding of the cellular responses implicated in perinatal brain damages and the characterization of the various mechanisms involved might open new horizons for understanding the time of onset of a brain hypoxic-ischemic lesion and for effective therapeutic strategies. Methods We performed an immunohistochemical investigation on brain and brainstem sections of 47 peripartum deaths. The gradation and localization of the expression of antibodies such as TNFα, IL-1β, IL-6, HSPs, β APP, anti-TrypH, GAP43, GFAP, COX2, ORP-150, could be correlated with an hypoxic-ischemic damage to document a significant correlation between response and the time of onset acute (≤8 hs) or non-acute (≥8 hs ≤48 hs). Results and Discussions In non-acute cases HSP70 reaction was prominent in the neuron cytoplasm, while in acute cases a mild reaction was evident in sporadic fields. HSP90 exhibited a similar pattern of positivity as HSP70. In acute group, ORP150 expressed an intense reaction showing a granular pattern in the cytoplasm of the neurons in the cortex of the infarcted areas. In non-acute group the positive reaction was more intense in astrocytes and less extended in neurons. COX2 reaction exhibited the strongest positive reaction in the neuronal cell bodies of acute cases, while a immunolabeling was prominent in the glial cytoplasm in the non-acute cases. Conclusions Chaperones HSP70 and 90, ORP-150 reaction, and COX2 protein, have provided very interesting results. These results would suggest to the clinicians to extend the differential diagnosis of a too large perinatal hypoxic-ischemic insult category to delineate a more accurate chronological judgement.